Murine Typhus: a Common Cause of Acute Febrile Illness with Potential for Serious Complications. (4th October 2017) - Afzal, Zeeshan; Kallumadanda, Sunand; Wang, Feng; Hemmige, Vagish S; Musher, Daniel
Abstract: Background: Individual cases and outbreaks of murine typhus have been documented in South Texas. We report 90 cases from Hidalgo County, Texas, enumerating complications and comparing results in children and adults. Methods: We reviewed records of 101 patients in three hospitals in Hidalgo County, Texas, who had positive typhus serology (IgG or IgM titer ≥1:128) during 3 years, 2014–2016 and were categorized as suspected, probable or confirmed murine typhus cases in accord with CDC definitions. We excluded 11 cases because a concurrent infection may have confounded our tabulation of manifestations or there was insufficient information to make a clinical diagnosis. Results: The majority presented with typical typhus: fever, headache, myalgias and fatigue. Rash, thrombocytopenia and elevated hepatic transaminases were frequent (Table). Clinical complications in 25 cases (28%) caused a less typical syndrome, including bronchiolitis, pneumonia, pancreatitis, cholecystitis, mesenteric adenitis, myositis, rhabdomyolysis, meningitis and septic shock. Procalcitonin was >0.5 in 10 of 14 (71%) cases. Once the diagnosis was suspected, patients were treated with doxycycline with a rapid response in every case. Generally fever disappeared within 24–36 hours of the first dose. Conclusion: Murine typhus is a common endemic infection in South Texas. Although most patients had a typical syndrome, the disease is multisystem, and complications appeared in 28% of cases. Procalcitonin was usually elevated. Rats and opossums are common reservoirs for Rickettsia typhi, and a search for cases of murine typhus may be warranted in other parts of the US as well, so that treatment with doxycycline can be begun promptly. Disclosures: All authors: No reported disclosures.